Acoustic radiation force impulse elastography of the spleen in healthy dogs of different ages - Maronezi, M. C. [UNESP]; Feliciano, M. A. R. [UNESP]; Crivellenti, L. Z. [UNESP]; Simoes, A. P. R. [UNESP]; Bartlewski, P. M.; Gill, I.; Canola, J. C. C. [UNESP]; Vicente, W. R. R. [UNESP] (Wiley-Blackwell, 2015)
OBJECTIVESTo determine the elastographic characteristics of splenic parenchyma in clinically healthy dogs of various ages in order to establish preliminary qualitative and quantitative standards/reference intervals for this technique.MATERIALS AND METHODSThirty three healthy dogs categorized as young, adult and elderly were used. Splenic echotexture, echogenicity, size and ages were assessed with B-mode ultrasonography. Using qualitative elastography, the spleen (head, body and tail) was examined for homogeneity and presence of deformities. Shear velocities in different splenic segments were then quantitatively evaluated.RESULTSAll splenic segments visualised with the B-mode ultrasonography appeared normal. Different splenic segments examined with qualitative elastography were free of any detectable malformations and the images appeared as homogeneous dark areas. The mean shear velocity values were 2.32 m/s for head, 2.16 m/s for body and 2.25 m/s for tail of the spleen (P = 0.40), and they did not vary between the different age groups (P > 0.05).CLINICAL SIGNIFICANCEQuantitative and qualitative ARFI elastography of the spleen in clinically healthy dogs differing in age could be easily performed, and it may aid in the diagnosis and evaluation of splenic abnormalities routinely assessed in veterinary practice with B-mode ultrasonography.